PAMERAN "DARI AKAL TURUN KE HATI" SEBAGAI BENTUK EKSISTENSI KEKINIAN SENI RUPA ISLAM INDONESIA - Endriawan, Didit (ATRAT: Jurnal Seni Rupa, 2024)
Since Islam entered and spread in Indonesia, its influence has been felt in many places and many fields. One of them is the field of fine arts which to this day still exists and is even developing in Indonesia. 90% of Indonesia’s population is Muslim so this is normal. As India has a majority of Hindu citizens, it is natural that Hinduism influences the way of life in India. The Islamic art exhibition “From the Mind to the Heart” is important evidence regarding the existence of contemporary Indonesian Islamic Art. The exhibition was held in the holy month of Ramadhan 1445 H, at Loman Park Hotel Jogjakarta. The characteristic of the exhibition “From the Mind Down to the Heart” is the sterility of depictions of animate creatures such as humans, animals and others, in other words, in accordance with Islamic law, artistic jurisprudence. This characteristic differentiates it from other or previous exhibitions but has the same spirit, namely preserving and even developing Islamic fine arts in Indonesia.